2018
DOI: 10.5539/jas.v10n11p171
|View full text |Cite
|
Sign up to set email alerts
|

Thai Purple Sweet Potato Flours: Characteristic and Application on Puffed Starch-Based Snacks

Abstract: Characteristics and properties of 4 Thai purple sweet potato flours, Maejo 343, Phichit 65-3, Phichit 290-9 and Torperk were determined in terms of native and pre-gelatinized flours. Color, physicochemical properties and antioxidant activity of native and pre-gelatinized flours depend on their varieties. All native flours showed low redness (a*) and blueness (-b*) values but high pasting properties. Pre-gelatinized flours had a unique purple color and high antioxidant activity. Flours produced by Phichit 65-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Similar results from this work on density were reported by Medeiros and Lannes (2010) when verified the physical properties of substitutes of cocoa in powder obtaining values of density varying between 0.49 and 0.69 g mL -1 . Phomkaivon et al (2018) when evaluating the flour of purple sweet potato obtained values of bulk density between 0.276 and 0.389 g cm -3 . Similar results for compacted density were reported by Lavoyer (2012) when studying the powder obtained from coconut, with values between 0.58 and 0.62 g mL -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Similar results from this work on density were reported by Medeiros and Lannes (2010) when verified the physical properties of substitutes of cocoa in powder obtaining values of density varying between 0.49 and 0.69 g mL -1 . Phomkaivon et al (2018) when evaluating the flour of purple sweet potato obtained values of bulk density between 0.276 and 0.389 g cm -3 . Similar results for compacted density were reported by Lavoyer (2012) when studying the powder obtained from coconut, with values between 0.58 and 0.62 g mL -1 .…”
Section: Resultsmentioning
confidence: 99%
“…When studying native flours of four PFSP varieties, Phomkaivon et al (2018) found significantly varied values, from L*, a*, and b*. In comparison with the flour in this study, the native flours of the four varieties showed lower values of a* (7.51, 11.66, 4.28, and 4.84) and b* (4.94, 1.58, 10.90, and 12.5) and higher L* (75.44, 66.85, 79.04, and 76.41), being lighter and less red flours.…”
Section: Colormentioning
confidence: 99%
“…Its use is already a reality. For example, it has already been incorporated into boiled pork sausage (Jin et al (2012), bread (Cui & Zhu, 2022;Mariano & Arruda, 2016), snacks (Phomkaivon et al, 2018), and noodles (Nurdjanah et al, 2022).…”
Section: Foaming Properties and Gel-forming Abilitymentioning
confidence: 99%
“…These foods are rich providers of carbs, protein, vitamins, minerals, fiber, and phytochemicals (Borges-Martínez et al, 2022;Kim et al, 2012;Zhang et al, 2022). The sweet potatoes deep purple color is due to the accumulation of anthocyanins which are capable of delivering a variety of biological functions, including free radical scavenging and anti-cancer properties (Phomkaivon et al, 2018). Some of the combined vegetables have many specific bioactive compounds, such as carotenoids and polyphenols have many biological properties, including antioxidant activity, anti-aging, anti-inflammatory, anti-viral, anti-bacterial, and anti-cancer (Li et al, 2016;Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%